Constraints to Local Government Performance n Agricultural Development in Anambra State, Nigeria - H. U. Nwalieji, et al (Journal of Agricultural Extension, 2013)
The purpose of the study was to identify constraints to local governments’ role performance in agricultural development in Anambra State of Nigeria. The population of the study consisted of all the local government staff in the agriculture and veterinary department in the 21 LGAs of Anambra State.  One management staff (head of department agriculture) and five (5) field staff from other cadres were purposively and randomly selected, respectively, giving a total of 60 respondents. Questionnaire and field observations were used for data collection. Frequency, percentage, mean score and factor analysis were used to analyze data. The mean age of the staff was 42.5years while majority (70.0%) was female and the mean of work experience was 18.33 years.  Most LGs’ roles in agricultural development had not been accomplished to great extent. Only provision of slaughter houses and slabs, establishment of market gardens, mobilization of farmers for cooperatives and procurement and distribution of fertilizer, improved seeds, improved seedlings, tractors and implements among others were perceived as accomplished to very great extent. All the 24 identified problems were serious, and four problems were factored as political, manpower, operational, and logistic problems.